Complementary atomic flame/molecular colorimetry dual-mode assay for sensitive and wide-range detection of cancer cells. Issue 27 (22nd March 2021) - Fang, Xueting; Zhang, Xiaoting; Zhang, Zhihua; Hu, Shengqiang; Ye, Fanggui; Zhao, Shulin
Abstract : A Sr 2+ -related complementary atomic flame/molecular colorimetry dual-mode and dual-ratiometric sensing platform for sensitive and wide-range point-of-care cancer cells testing. Abstract : Since multicolor switch was involved in both Sr 2+ -related flame and precipitation reactions, these reactions can be thus utilized for constructing a complementary atomic flame/molecular colorimetry dual-mode sensing platform for a sensitive and wide-range analysis of cancer cells by virtue of the gas generation from platinum nanozyme-mediated hydrogen peroxide decomposition.